Insight into the codon usage patterns and adaptation of Tembusu Virus - Fucheng Guo; Huiming Tan; Jinjin Yang; Rumin Jia; Ruichen Wang; Lie Wu; Fengzhi Pan; Kai Kang; Weitian Xie; Youquan Li; Kewei Fan (Poultry Science)
Since its emergence in 2010, Tembusu virus (TMUV) has rapidly spread across poultry populations in Asia, leading to substantial economic losses in these areas. Here, we investigate the codon usage patterns (CUPs) underlying TMUV's adaptation and evolutionary dynamics within host environments. Phylogenetic and compositional analyses consistently classify TMUV into four evolutionary lineages—Clusters 1, 2, 3, and ancestral TMUV—with Cluster 2 emerging as the dominant lineage. Codon adaptation index (CAI) analysis reveals that this lineage of TMUV show best adapted to the CUPs of duck than other lineages, underscoring the role of natural selection in shaping viral evolution, a finding in line with evidence that CUPs in the TMUV genome is predominantly shaped by natural selection. Furthermore, TMUV exhibits markedly higher adaptation to the CUPs of poultry hosts (duck, goose, and chicken) compared to potential host humans or vector mosquito. Thus, species-specific adaptability to the host environment may be a reason account for the distinct infectivity and clinic outcome of TMUV acted on hosts. Analysis of dinucleotide distribution reveals significant suppression of CpG and UpA dinucleotides in the TMUV genome, reflecting adaptive pressures to evade vertebrate immune responses. During transmission, TMUV shows increasing alignment with host CUPs and a continuous reduction in CpG dinucleotides, potentially enhancing its fitness within host microenvironments. This work advances our understanding of the basic biology underlying TMUV epidemiology, pathogenicity, and species-specific adaptation.